Estimating the Impact of Oil Price Volatility on the Ecuadorian Economy: A MIDAS Approach - Camacho-Villagomez, Freddy Ronalde; Bajaña-Villagomez, Yanina Shegia; Rodríguez-Bustos, Andrea Johanna (International Journal of Energy Economics and Policy, 2024)
This paper provides empirical evidence about the impact of oil price volatility on government spending, tax revenues, and economic growth for Ecuador. The effects are estimated via a MIDAS regression using quarterly and monthly data for the period 2004 to 2019. The results show that oil price volatility has a positive impact on government spending and tax revenues which is an indicative of a non-prudence behavior in fiscal policy. The impact of GDP is non-significant, contrary to economic intuition and previous studies. These findings have several policy implications that are consistent with the literature of fiscal policy in oil-exporting countries.